Buffer stocks for gum - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Chad, Nigeria and Sudan have agreed to set aside the equivalent of a year s production of gum arabic (a total of around 40,000 t)...